Potret Kondisi Sosial Perempuan pada Film Holy Spider Karya Ali Abbasi - Nur Fatimah Sutomo (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This study aims to analyze in regard of women's social conditions in the film Holy Spiderdirected by Ali Abbasi. Using a descriptive qualitative approach based on Simone de Beauvoir's theory of women's position, Erving Goffman's theory of stigma, Michel Foucault's theory of power, and the sociology of literature approach, this research reveals how Holy Spiderrepresents gender inequality and the oppression of women within Iran's social structure. The characters Rahimi, a journalist, along with Somayeh and Soghra, who are sex workers, illustrate how women experience restricted mobility, violence, discrimination, and social marginalization. The findings show that the portrayal of women's social conditions in the film not only reflects the social realities in Iran but also highlights how power and social norms contribute to reinforcing injustice against women. Through this film, Abbasi presents the harsh reality faced by women living under a rigid patriarchal system that denies space for gender equality.